2016
DOI: 10.1007/s11130-016-0547-4
|View full text |Cite
|
Sign up to set email alerts
|

Feruloylated Oligosaccharides from Maize Bran Modulated the Gut Microbiota in Rats

Abstract: Corn bran is a byproduct produced from corn milling; it is rich in ferulic acid and hemicellulose. In this research, the effects of feruloylated oligosaccharides (FOs) from maize bran on the microbial diversity and profiles in rat feces were investigated through 16S rRNA sequencing. FOs significantly increased bacterial richness and diversity compared with the control and xylooligosaccharides (XOS) alone. In comparison with the control group and the group administrated with XOS, FOs orally administered at 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 25 publications
4
57
1
Order By: Relevance
“…These data revealed that feeding rats a blend of the three nutrients is better than feeding any single prebio tics. These fi ndings are similar to the very recent report that feruloylated xylooligosaccharides showed even higher prebiotic activity than xylooligosaccharides obtained by detecting microbiota profi les in rat faeces through 16S rRNA sequencing (OU et al, 2016).…”
Section: In Vivo Batch Fermentationsupporting
confidence: 91%
“…These data revealed that feeding rats a blend of the three nutrients is better than feeding any single prebio tics. These fi ndings are similar to the very recent report that feruloylated xylooligosaccharides showed even higher prebiotic activity than xylooligosaccharides obtained by detecting microbiota profi les in rat faeces through 16S rRNA sequencing (OU et al, 2016).…”
Section: In Vivo Batch Fermentationsupporting
confidence: 91%
“…Previous studies found that Lactobacillus decreased in diabetic rats ( Yan et al, 2016 ) and HF rats ( Lau et al, 2016 ). Inclusion of feruloylated oligosaccharides from maize bran in the normal diet of rats increased Lactobacillus in fecal microbiota ( Ou et al, 2016 ). Whole wheat consumption was associated with a three-fold higher abundance of Lactobacillus compared to both obese and lean control mice ( Garcia-Mazcorro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanism underlying the effect of FOs on the formation of volatiles Jiang et al [1] found that ferulic acid, which acts as an antioxidant, can inhibit the formation of Maillard volatiles by scavenging Maillard-type reactive radical precursors (i.e., dialkylpyrazine radical), or direct the formation of adducts with Maillard reaction intermediates FOs, which have higher antioxidant activity than free ferulic acid, [5] may have inhibited the formation of Maillard Values (means ± SD, n = 3) with different letters within a line are significantly different at the 5% level.…”
Section: Effect Of Fos On Volatile Formation In the Dough Modelmentioning
confidence: 99%
“…[1,2] Even at lower temperatures (60°C or 37°C), ferulic acid significantly inhibits the Maillard reaction. [3,4] Feruloylated oligosaccharides (FOs) are water-soluble prebiotics [5] and emulsifiers [6] , formed by the esterification of oligosaccharides and exhibit the physiological properties of both ferulic acid and oligosaccharides. [7,8] FOs have been approved by the US FDA as a wheat bran extract and can be added to various foods, including bakery foods.…”
Section: Introductionmentioning
confidence: 99%